Determination of Trace Lead with Cloud Point Extraction Precipitation Method - Zhao, Yan; Zhang, Xiaoxia; Ma, Yuqin; Ouyang, Shaohu (Asian Journal of Chemistry, 2015)
This work presented the determination of lead with Na2S as precipitant and with the cloud point phenomenon of Triton X-114 to separate the precipitate and then determine the trace amount of lead by atomic adsorption spectrometry. This method has remarkable advantages compared with the traditional method. This test optimized the determination condition and the selectivity of this method was studied. The regression equation is found: A = 0.0623 C (μg/25 mL) + 0.003, the correlation coefficient is r = 0.9998, the linear range is 1-320 μg/L, the lead detection limit is CL = 1 μg/L(n = 11). The method is applied for concentration determination of trace amount of lead in samples of water, tea and pollen. The relative standard deviations is 1.19-5.60 % and the standard recovery is 92-106 %.